When Any Sentence is a Life Sentence: Employment Discrimination Against Ex-Offenders - Dallan F. Flake (Washington University Law Review, 2015)
For the sixty-five million Americans with a criminal record, it is cruelly ironic that perhaps the most important resource for turning their lives around—employment—is also often the most elusive. Shut out from legitimate job opportunities, many ex-offenders resort to illegal means of survival that hasten their return to prison. Recidivism has devastating consequences not only for the individual offender, but also the family, the community, and society at large. This article proposes three amendments to Title VII of the Civil Rights Act of 1964 that seek to balance ex-offenders’ need for employment with employers’ safety concerns. First, employers should be prohibited from discriminating against an ex-offender whose criminal record is not directly related to the job in question or who does not pose an unreasonable threat to property or to the safety of others. Second, employer inquiries about an applicant’s criminal record should be delayed until after at least one job interview. Third, a negligent hiring provision should be added to Title VII that creates a rebuttable presumption against negligence and that caps damages in certain cases. These measures represent a sensible, middle-of-the-road approach that promotes the employment of ex-offenders in appropriate cases, while ensuring that neither employers nor the public are unduly burdened as a result.
Keywords: Employment Law; Employment discrimination; Offender re-entry; Title VII; Civil Rights Act; Criminal record; Job interview; Recidivism